2017
DOI: 10.21608/zvjz.2017.7891
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin M1 in Milk and some Dairy Products: Level, Effect of Manufature and Public Health Concerns

Abstract: Aflatoxins (AFs) are toxic and carcinogenic metabolites produced by a variety of fungi. Aflatoxin M1 (AFM1) is the major carcinogenic type frequently found in milk and dairy products, thus posing a significant impact on human health. The current study was undertaken to examine milk and some dairy products for contamination with AFM1 in local markets, Sharkia Governorate, Egypt, as well as the effect of manufacture. A total of 75 samples (15, each) of raw milk, pasteurized milk, yoghurt, processed cheese and Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
4
7
2
Order By: Relevance
“…On the other hand, of the 48 natural yogurts tested, only 2 80%, respectively [45]. Several studies were carried out concerning the effect of yogurt manufacturing on AFM1 content, whereas some projects were reported with no influence on aflatoxin M1 concentration [46]. In contrast to our study which found a high frequency of AFM1 contamination in all yogurt samples, the previous studies discovered variable concentrations of aflatoxin M1 in yogurt compared to the milk.…”
Section: Yogurt Samplescontrasting
confidence: 99%
“…On the other hand, of the 48 natural yogurts tested, only 2 80%, respectively [45]. Several studies were carried out concerning the effect of yogurt manufacturing on AFM1 content, whereas some projects were reported with no influence on aflatoxin M1 concentration [46]. In contrast to our study which found a high frequency of AFM1 contamination in all yogurt samples, the previous studies discovered variable concentrations of aflatoxin M1 in yogurt compared to the milk.…”
Section: Yogurt Samplescontrasting
confidence: 99%
“…The same results were reported by El Khoury et al [30], Montaseri et al [31], and Tahoun et al [9]. On the other hand, Iha et al [32] reported that the fermentation process of yoghurt manufacture has no effect on AFM1.…”
Section: Resultssupporting
confidence: 82%
“…Various chemical, physical, and biological agents have been used to detoxify aflatoxins from food and feed materials. But, elimination of AFM1 from milk with physical and chemical methods have some disadvantages, such as losing its nutritional value, insufficiency of toxin elimination with high costs [9]. Thus, an effective and practical method is needed to be developed for the detoxification of AFM1 contaminated milk.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, unmodified AFM1 is excreted through urine or milk [27][28][29][30]. Because of its excretion in milk, AFM1 contamination in dairy products is a serious concern, as it might pose severe health risks for humans in general and for susceptible population groups such as infants and young children [28,31]. Hence, the full characterization of AFB1 mechanistic toxicology in dairy cattle, together with the possible tools to reduce its consequences in humans in animals and humans, is gaining increasing interest in the scientific community.…”
Section: Introductionmentioning
confidence: 99%